Effectiveness of a web-based cognitive behavioral self-help intervention for Binge eating disorder: a randomized clinical trial - Prüßner, Luise; Timm, Christina; Barnow, Sven; Rubel, Julian; Lalk, Christopher; Hartmann, Steffen (JAMA network open, 2024)
Binge eating disorder (BED) is one of the most frequent eating pathologies and imposes substantial emotional and physical distress, yet insufficient health care resources limit access to specialized treatment. Web-based self-help interventions emerge as a promising solution, offering more accessible care.To examine the effectiveness of a web-based cognitive behavioral self-help intervention for individuals with BED.This 2-arm, parallel-group randomized clinical trial conducted from January 15, 2021, to August 3, 2022, in Germany and other German-speaking countries enrolled patients aged 18 to 65 years who met the diagnostic criteria for BED (according to the Diagnostic and Statistical Manual of Mental Disorders [Fifth Edition]). Data analysis occurred between January 27 and September 4, 2023, following our statistical analysis plan.Participants were randomized to a web-based self-help intervention or a waiting-list control condition.The primary outcome was a change in objective binge eating episodes from baseline to after treatment. Secondary outcomes included global eating pathology, clinical impairment, work capacity, well-being, comorbid psychopathology, self-esteem, and emotion regulation.A total of 1602 patients were screened, of whom 154 (mean [SD] age, 35.93 [10.59] years; 148 female [96.10%]) fulfilled the criteria for BED and were randomized (77 each to the intervention and control groups). The web-based intervention led to significant improvements in binge eating episodes (Cohen d, −0.79 [95% CI, −1.17 to −0.42]; P < .001), global eating psychopathology (Cohen d, −0.71 [95% CI, −1.07 to −0.35]; P < .001), weekly binge eating (Cohen d, −0.49 [95% CI, −0.74 to −0.24]; P < .001), clinical impairment (Cohen d, −0.75 [95% CI, −1.13 to −0.37]; P < .001), well-being (Cohen d, 0.38 [95% CI, 0.01 to 0.75]; P = .047), depression (Cohen d, −0.49 [95% CI, −0.86 to −0.12]; P = .01), anxiety (Cohen d, −0.37 [95% CI, −0.67 to −0.07]; P = .02), self-esteem (Cohen d, 0.36 [95% CI, 0.13 to 0.59]; P = .003), and emotion regulation (difficulties: Cohen d, −0.36 [95% CI, −0.65 to −0.07]; P = .01 and repertoire: Cohen d, 0.52 [95% CI, 0.19 to 0.84]; P = .003).In this randomized clinical trial of a web-based self-help intervention for patients with BED, the findings confirmed its effectiveness in reducing binge eating episodes and improving various mental health outcomes, highlighting a scalable solution to bridge the treatment gap for this condition.ClinicalTrials.gov Identifier: NCT04876183